Women wrestling at the Paris 2024 Olympic Games - Grigore, E.-A.; Talaghir, L.-G.; Moisescu, P.; Grigore, A. (Annals of "Dunarea de Jos" University of Galati: Physical Education and Sport Management, 2025)
Women wrestling at the Paris 2024 Olympic Games (participation area, dominant nations, champions and other milestones). The paper addresses the women's wrestling competition at the Olympic Games, Paris 2024, trying to establish the trends of participation in the most recent Olympic competition. The research establishes, based on statistical analysis, the origin of the athletes who qualified for the Olympic competition, both from the perspective of continents, but also of the countries of origin. At the same time, by counting the performances obtained, we were able to establish the dominant nations in women's wrestling, in general, as well as in each Olympic weight category, in particular ... The paper also establishes whether the number of qualified athletes is decisive for achieving dominance in terms of top performances (rankings by nations and continents). Based on the correlation of the 3 Olympic qualifying competitions, the Continental Qualification Tournament, the World Qualification Tournament and the World Championship, with the results obtained at the Olympic competition, the paper identifies whether the timing of qualification influences the Olympic course and implicitly the pre-competitive planning of the activity of top female wrestlers. The present paper represents a starting point for future research in order to establish a pattern of technical-tactical manifestation of the Olympic champion, the period necessary to reach maximum potential and implicitly the optimal moment of selection as a consequence of the period of practice necessary to reach this potential.